Interactive E-module Based on H-Guided Inquiry: Optimize the ICT Skills and Learning Achievements - Nur Rohmah Utami; Akhmad Jufriadi; Hena Dian Ayu (Berkala Ilmiah Pendidikan Fisika, 2020)
This study aimed to optimize the ICT skills and the learning achievement of the students on the subject of the regular circular motion through the development of the interactive e-module that is based on the Hybrid Guided Inquiry with good criteria. As a result, it could be utilized to help the learning process in class. The learning and development model used was the ADDIE model that stood for Analyze, Design, Development, Implementation, and Evaluation to generate the interactive e-module that could be utilized in the learning process based on the expert’s assessment. The final result of the e-module development revealed that it was included in a good category with the content eligibility score was 3.58, and the language eligibility score was 3.4. Meanwhile, the percentage of the ideals score of the interactive module was 87.1%. The result of the small-scale assessment on the 26 of students was 3.32 within the “good” category.  The N-gain score that was utilized as the proving suggestions of the ICT skill optimization was 0.85 that was included into ”high” category, and 0.61 for the achievement optimization of the students that were categorized into “medium” category after being given the treatment. In this way, the interactive e-module that is based on Hybrid Guided Inquiry on the subject of the regular circular motion was feasible to be utilized as the learning media in class. It was also effective to ease the learning process in optimizing the ICT skills and the learning achievements of the students.